2006
DOI: 10.1098/rsta.2006.1777
|View full text |Cite
|
Sign up to set email alerts
|

Activation sequence as a key factor in spatio-temporal optimization of myocardial function

Abstract: Using one-dimensional models of myocardial tissue, implemented as chains of virtual ventricular muscle segments that are kinematically connected in series, we studied the role of the excitation sequence in spatio-temporal organization of cardiac function. Each model element was represented by a well-verified mathematical model of cardiac electro-mechanical activity. We found that homogeneous chains, consisting of identical elements, respond to non-simultaneous stimulation by generation of complex spatio-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Besides, relative to "slow" muscle Са 2+ transition to a faster virtual muscle has a rapid contraction and shorter duration of action potential. At the same time, pacing of the "fast" muscle reduces the contractility of the myocardium, but pacing of the "slow" onechanges insignificantly [30,[34][35][36]. Thus, we can assume that the electrical pacing of the ventricular area with longer ARIs does not change the contractility, while pacing of the ventricular area with shorter ARIs leads to the reduction of the pump function of the heart.…”
Section: The Effects Of the Repolarization Durations On The Indices Omentioning
confidence: 95%
See 2 more Smart Citations
“…Besides, relative to "slow" muscle Са 2+ transition to a faster virtual muscle has a rapid contraction and shorter duration of action potential. At the same time, pacing of the "fast" muscle reduces the contractility of the myocardium, but pacing of the "slow" onechanges insignificantly [30,[34][35][36]. Thus, we can assume that the electrical pacing of the ventricular area with longer ARIs does not change the contractility, while pacing of the ventricular area with shorter ARIs leads to the reduction of the pump function of the heart.…”
Section: The Effects Of the Repolarization Durations On The Indices Omentioning
confidence: 95%
“…This mechanism involves the change in the duration of local repolarization and homeostasis of cardiomyocytes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an experimental approach to studying biomechanical and bioelectrical properties of heterogeneous system consisting of two different units [9]. By the muscle duplex method it obtained some important features of the contractile function of interacting segments in heterogeneous myocardium [10]- [12]. Though the experimental study of heterogeneous systems consists of greater number of units, it is an awkward task to date.…”
Section: Introductionmentioning
confidence: 99%
“…We have earlier created mathematical models to study the effects of electrical and mechanical interactions between myocardial tissue segments [23] including a muscle duplex approach and discrete chain models, where two or several cardiac muscle segments connected in-series or in-parallel interact mechanically with each other [23,24]. In the framework of these discrete models we showed that the time lag in electrical excitation of the segments actually intrinsic to the activation of various region of the heart wall resulted in gradual changes in their behavior producing functional heterogeneity of the myocardium system [17].…”
Section: Introductionmentioning
confidence: 99%